Resected pancreatic cancer outcomes in the elderly. Issue 2 (March 2015) - Frakes, Jessica M.; Strom, Tobin; Springett, Gregory M.; Hoffe, Sarah E.; Balducci, Lodovico; Hodul, Pamela; Malafa, Mokenge P.; Shridhar, Ravi
Abstract Objective To determine if age affects outcome in patients with resected pancreatic head cancer. Materials and Methods An IRB-approved pancreatic cancer database was queried for patients with upfront resected pancreatic head cancer treated at our institution between 2000 and 2012. Overall survival (OS) curves were calculated according to the Kaplan–Meier method and log-rank analysis. Multivariate analysis was performed using the Cox proportional hazard model. Results We identified 193 patients. Patients ≥ 70 years were less likely to receive adjuvant treatment (p = 0.002); however there were no other significant differences between age groups. There was a trend towards increased pancreatic leaks in the elderly group (p = 0.06), but no difference in post-operative complications or mortality. There was no difference in overall survival based on age. Median and 5-year OS were 23 months and 26.7% in patients < 70 years, 23.4 months and 23% in those 70–75 , 16.1 months and 0% in those 76–80, and 18.7 months and 15.4% in those > 80 years (p = 0.62). On univariate analysis, there was increased OS in patients with lower T stage, N0 status, post-operative CA19-9 level < 90, and use of chemoradiotherapy (p < 0.05). Multivariate analysis revealed that lower tumor stage, N0, post-operative CA19-9 level < 90, and use of any adjuvant therapy predicted decreased mortality (p < 0.05). Age, gender, tumor site, tumor grade, and positive margins were not prognostic on multivariate analysis. Conclusions There is no difference in outcomes when comparing elderly patients with resected pancreatic cancer to those patients < 70 years of age.